2017
DOI: 10.18537/mskn.08.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad genética de accesiones de la familia Caricaceae en el sur de Ecuador

Abstract: x heilborne cv chrysopetala, Carica papaya, Jaracatia digitata y J. spinosa, a través de la amplificación de los ADN con 14 iniciadores aleatorios de las series AA, AC, AM y AN de Operon Technologies Inc. Los iniciadores RAPD utilizados para la amplificación produjeron un total de 76 fragmentos polimórficos con tamaños entre 368 y 2102 pares de base (pb). Los análisis de cluster y coordenadas principales agruparon las accesiones de cada especie entre ellas y fueron consistentes en su mayoría con otros estudios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Vasconcellea is a plant genus within the Caricaceae family, naturally occurring in the subtropical regions of South America, especially in the high regions of Colombia and Ecuador. Ecuador harbors at least 16 of the 21 Vasconcellea species previously described [17]. In 2020, Tineo et al [18] identified 5 new Vasconcella species in Peru through the sequencing of six marker genes, expanding the total count of species within this genus to 26.…”
Section: Introductionmentioning
confidence: 99%
“…Vasconcellea is a plant genus within the Caricaceae family, naturally occurring in the subtropical regions of South America, especially in the high regions of Colombia and Ecuador. Ecuador harbors at least 16 of the 21 Vasconcellea species previously described [17]. In 2020, Tineo et al [18] identified 5 new Vasconcella species in Peru through the sequencing of six marker genes, expanding the total count of species within this genus to 26.…”
Section: Introductionmentioning
confidence: 99%